2022
DOI: 10.1136/jmg-2022-108675
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of very early treated infantile-onset Pompe disease with short-term steroid premedication: experiences from a nationwide newborn screening programme

Abstract: BackgroundStarting enzyme replacement therapy (ERT) before severe irreversible muscular damage occurs is important in infantile-onset Pompe disease (IOPD). This long-term follow-up study demonstrates our diagnostic and treatment strategies for IOPD and compares our clinical outcomes with those of other medical centres.MethodsIn this long-term follow-up study, we analysed the outcomes of very early ERT with premedication hydrocortisone in patients with IOPD. Out of 1 228 539 infants screened between 1 January 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Of the Taiwanese CRIM-positive IOPD cohort, 26 patients were followed for an average of 6.18±3.14 years. All patients included in the study had normal heart sizes, achieved typical motor milestones, demonstrated intact cognitive function, and displayed pulmonary function that ranged from near-normal to normal [ 145 ]. Long-term study in one of the largest cohort of IOPD in France recently showed fewer benefits of ERT, with only temporary improvements followed by muscle and respiratory function deterioration; however, the impact of the age of ERT initiation was not explicitly assessed [ 146 ].∥Real-world data in patients who were either pre-symptomatic or lacked clinical or chemical signs of deterioration demonstrate the benefit of higher doses of ERT (e.g., 40 mg/kg every other week and 20 mg/kg weekly) early in life [ 147, 148 ].…”
Section: Neuromuscular Diseases With Evidence Supporting Benefits Of ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Of the Taiwanese CRIM-positive IOPD cohort, 26 patients were followed for an average of 6.18±3.14 years. All patients included in the study had normal heart sizes, achieved typical motor milestones, demonstrated intact cognitive function, and displayed pulmonary function that ranged from near-normal to normal [ 145 ]. Long-term study in one of the largest cohort of IOPD in France recently showed fewer benefits of ERT, with only temporary improvements followed by muscle and respiratory function deterioration; however, the impact of the age of ERT initiation was not explicitly assessed [ 146 ].∥Real-world data in patients who were either pre-symptomatic or lacked clinical or chemical signs of deterioration demonstrate the benefit of higher doses of ERT (e.g., 40 mg/kg every other week and 20 mg/kg weekly) early in life [ 147, 148 ].…”
Section: Neuromuscular Diseases With Evidence Supporting Benefits Of ...mentioning
confidence: 99%
“…Cipalglucosidase alfa (Pombiliti ® ) is another ERT, used in combination with miglustat [108]. Avalglucosidase alfa was shown to be a safe and efficient alternative to alglucosidase alfa in LOPD [109][110][111] and has received marketing authorization in several countries for LOPD and/or IOPD, whereas cipaglucosidase alfa has received recent approval for adult LOPD [145]. Results from the mini-COMET trial suggest that avalglucosidase alfa is beneficial in IOPD patients who are less than 18 years of age who were declining on alglucosidase alfa [112], but the timing of treatment was not specifically evaluated.…”
Section: Pompe Diseasementioning
confidence: 99%
“…Enzyme analyses on leukocytes/lymphocytes, biochemical assays demonstrating accumulation and gene analyses can confirm the clinical diagnosis [ 5 , 6 ]. The treatment (enzyme-replacement therapy ERT, hematopoietic stem-cell transplantation HSCT, chaperones and gene therapy) can significantly improve outcomes, but the progressive nature of these diseases makes early diagnosis essential [ 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%